SOCIALIZATION OF THE APPLICATION OF GEOMEMBRANE TECHNOLOGY IN PEOPLE'S SALT PRODUCTION AND MARKETING STRATEGY IN KUALA CANGKOY VILLAGE FIELD DISTRICT NORTH ACEH REGENCY - Asbar, Yuli; Iswadi, Iswadi; Mahdaliana, Mahdaliana; Ula, Mutammimul; Razif, Razif (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
Socialization of service is aimed at salt farmers in developing geomembrane technology for smallholder salt businesses in accordance with local resource conditions and capacities, potential and capacity for salt development and marketing, and the availability of technology to increase sales of salt based on information technology, as well as technical management capabilities in one management. The problem with salt farmers is mostly coastal communities which are identical with helplessness, poverty and backwardness, especially from the socio-economic aspect. Traditional production technology, small production scale, and limited marketing and promotion strategies cause the products they produce are still far from prosperous due to low income. The low income of salt farmers makes it difficult for salt farmers to implement innovations and increase the productivity of salt farmers in various regions. The objectives of implementing science and technology activities for the community (PKM) are, firstly, geomembrane technology to increase the resource capacity of salt farmers in an effective and efficient manner, secondly to increase sales marketing results of salt production, thirdly to increase sales significantly through information technology promotion media, fourthly to create shelters. Ergonomically salt in Kuala Cangkoy, Lapang District. The specifications of the socialization results from community service produced can achieve economies of scale and be able to have salt carried out in an integrated manner in the marketing management system. Have a strong bargaining position in the market, both the primary product market and its derivative products based on information technology technology. The last is being able to increase the income of partner members collectively from the results of storing salt because the place is built according to ergonomic principles and from a marketing perspective.